Triple tubostomy and its outcome for blunt duodenal injury - Pandit, Narendra; Yadav, Tek Narayan; Awale, Laligen; Adhikary, Shailesh (Journal of Society of Surgeons of Nepal, 2019)
Introduction: Blunt duodenal injury in an uncommon form of abdominal injuries, which comprises less than 5% of all injuries. The diagnosis and management are challenging, because of delays in diagnosis due to subtle signs and symptoms in its early stage of presentation. Primary repair along with triple tubostomy (gastrostomy, retrograde duodenostomy and feeding jejunostomy) is a simple and safe method of damage control surgery in this group of patients. This study aims to report our experience in the management of this uncommon procedure. Methods: This is a retrospective analysis of the patients undergoing triple tubostomy (TT) for blunt duodenal injury at the Department of Surgery, B.P.Koirala Institute of Health Sciences (BPKIHS), Dharan, over a three and half years. The study included demographics, clinical profile, length of hospital stay, postoperative morbidity (duodenal fistula), rate and timing of spontaneous closure of fistula and mortality. Results: Eleven (6.7%) patients out of 164 blunt trauma abdomen had sustained a duodenal injury. Eight patients who underwent TT were included in the study. The mean age of the patient was 31.8 years (range: 18-67), with a male: female ratio of 3:1. The mean time to trauma and presentation was 4.25 days. The most common site of injury was the second part of the duodenum (87.5%), AAST grade III was seen in 62.5%, two (25%) patients were in shock at presentation. Eight patients required primary closure with triple tubostomy. Postoperatively, all patients had a duodenal fistula, which closed spontaneously in 6 (75%) patients at a mean duration of 17 days, with a mean postoperative length of hospital stay of 33.5 days. The remaining two (25%) patients died of an active fistula. Conclusion: Blunt duodenal trauma, when presented late can be managed with primary closure and triple tubostomy with acceptable postoperative outcomes.